2019
DOI: 10.1007/s10479-018-03130-w
|View full text |Cite
|
Sign up to set email alerts
|

Partial commitment in an endogenous timing duopoly

Abstract: A duopoly game with timing announcements endogenizes the sequence of commitments. In duopolistic price competition, endogenous moves lead to a coordination problem with two non-Pareto ranked subgame perfect equilibria (SPEs). In these SPEs both firms prefer followership to leadership. We suggest that a unique SPE can be found if firms use partial commitments to their timing announcements. Using partial commitments, the firms first announce the timing of moves but reserve the option to deviate from this announc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…They showed that countries will finally reach a simultaneous equilibrium if both decide to be the first movers in the game. Leppänen (2020) studied partial commitments in a duopoly associated with endogenous timing. He showed that both countries would prefer to be followers rather than leaders under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that countries will finally reach a simultaneous equilibrium if both decide to be the first movers in the game. Leppänen (2020) studied partial commitments in a duopoly associated with endogenous timing. He showed that both countries would prefer to be followers rather than leaders under certain conditions.…”
Section: Introductionmentioning
confidence: 99%